Effect of inactivated and mRNA COVID-19 vaccines on thrombocytopenia in immune thrombocytopenia patients Efecto de las vacunas inactivada y de ARNm contra la COVID-19 sobre la trombocitopenia en pacientes con trombocitopenia inmunitaria - SEZEN, DUYGU; YANIK, AHMET MERT; TOPTAŞ, TAYFUR; YILMAZ, ASU FERGÜN (My University, 2024)
This retrospective observational study was aimed to address the possible effects of inactivated and mRNA vaccines in immune thrombocytopenia patients related to exacerbation. To define exacerbation, more than 30% decrease in platelet counts from baseline or platelet counts decreased to less than 30×109/L and/or development of new bleeding were considered. Fifty-nine (male 30.5%, female 69.5%) out of 208 immune thrombocytopenia patients, were enrolled in the study. The median age was 47 (range18-86). A total of 171 vaccinations were performed in 59 patients. Thirty-eight and 62% of patients were vaccinated with Sinovac® and BioNTech®, respectively. Overall, 10 (16.9%) patients experienced decrease in platelet count below 30×109/L after vaccination. During the last year before pandemic, 19 of the same cohort (32.2%) experienced such decrease. After first, second and booster dose vaccinations, 12.7%, 13.8% and 15% of patients experienced exacerbation respectively; exacerbation with minor bleeding was 2.3% and all bleeding episodes were successfully treated by starting with steroid or increasing the steroid dose. We did not report any severe and life-threatening bleeding. A statistical difference in exacerbation was documented in patients vaccinated with mRNA vaccine (p =0.041) only after the first dose and younger patients experienced a higher rate of exacerbation without statistical significance (p=0.06) after the first dose. In conclusion, both mRNA and inactivated vaccines seem to be safe for immune thrombocytopenia patients with rare bleeding complications. Especially younger patients and those vaccinated with mRNA vaccines should be followed up closely for 1-2 months post vaccination for thrombocytopenia.
Keywords: Tıp; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (Med); Yaşam Bilimleri (Life); Klinik Tıp; İmmünoloji; Moleküler Biyoloji Ve Genetik; Mikrobiyoloji; Alerji; Biyokimya Ve Moleküler Biyoloji; Biyoteknoloji Ve Uygulamalı Mikrobiyoloji; Clinical Medicine (Med); Life Sciences (Life); Clinical Medicine; Immunology; Molecular Biology & Genetics; Microbiology; Allergy; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; İmmünoloji ve Alerji; Moleküler Tıp; İlaç Keşfi; Immunology and Allergy; Molecular Medicine; Drug Discovery; COVID-19; immune thrombocytopenia; SARS-CoV-2; vaccination; vaccines